Development and Validation of Boceprevir using Stability Indicating Reversed-Phase High-Performance Liquid Chromatography Method with Diode Array Detector - Shilpi Pathak, (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Nowadays, demands for anti-viral drugs have significantly increased in recent years because of global susceptibility to viral infections, notably the COVID-19 pandemic and now emergence of human metapneumovirus. Ensuring quality standards and validation of these drugs is essential in healthcare. Boceprevir (BCP) is an antiviral drug classified as a protease inhibitor, primarily used to treat chronic hepatitis C virus infection, with a particular focus on genotype 1. Objective: The primary objective is to provide a reversed-phase high-performance liquid chromatography (RP-HPLC) method for the analysis of BCP that is simple, reliable, accurate, and rapid, and to validate it as per ICH guidelines with stability-indicating studies. Materials and Methods: The chromatographic analysis was performed using Ainertsil ODS-3V, C18 (250 mm × 4.6 mm, 5 μm) by GL Sciences. The mobile phase comprised acetonitrile: methanol and buffer (0.05 M potassium dihydrogen phosphate) in a 50:40:10 (v/v/v) ratio, with an adjusted pH of 3.5 using orthophosphoric acid. The flow rate was maintained at 0.25 mL/ min, with column temperature set at 25°C. Detection was conducted at 206 nm, and the injection volume was 20 μL. Results: The BCP exhibited a retention time of 3.69 min. The method demonstrated outstanding linearity within the concentration range of 10–50 μg/mL, with a correlation coefficient (r2) value of 0.9998.Validation parameters were evaluated following ICH Q2 guidelines, including limit of detection, limit of quantification, accuracy, precision, robustness, and ruggedness. The % relative standard deviation for all parameters was <2%. The stability-indicating method revealed small degradation products under forced degradation conditions, confirming the method’s specificity and selectivity. Conclusion: The developed RP-HPLC method demonstrated a high theoretical plate count, good resolution, and a symmetric peak, ensuring its accuracy, linearity, specificity, selectivity, and robustness. The method is suitable for detecting impurities and assessing degradation products during the forced degradation study. The validated method is suitable for repetitive pharmaceutical quality control examination and safety assessment of BCP.